A generalised vibronic-coupling Hamiltonian model for benzopyran - Joubert-Doriol, Loïc; Lasorne, Benjamin; Lauvergnat, David; Meyer, Hans-Dieter; Gatti, Fabien (The journal of chemical physics, 2014)
A new general model for describing intersecting multidimensional potential energy surfaces when motions of large amplitude are involved is presented. This model can be seen as an extension of the vibronic coupling models of Köppel et al. [“Multimode molecular dynamics beyond the Born-Oppenheimer approximation,” Adv. Chem. Phys. 57, 59 (1984)]. In contrast to the original vibronic coupling models, here the number of diabatic states is larger than the number of adiabatic states and curvilinear coordinates are used in a systematic way. Following general considerations, the approach is applied to the fitting of the potential energy surfaces for the very complex nonadiabatic photodynamics of benzopyran. Preliminary results are presented at the complete active space self-consistent field level of theory and with up to 12 active degrees of freedom. Special emphasis is placed on the physical interpretation of the diabatic states and on the influence of the various degrees of freedom on the fit.
Gesehen am 12.10.2020